Innovation of a Grinder Machine for Improvement of Waste Treatment for Craftsmen at Mayong Lor Village, Jepara - Putri Purwaningrum, Jayanti; Purbasari, Imaniar; Puspita Rini, Gilang (KnE Social Sciences, 2022)
Mayong Lor Village has superior regional products in the form of pottery crafts, such as traditional children’s toys, jars, and others. Other clay-based businesses include producing roof tiles, wuwung and bricks. The main problem for craftsmen is the amount of waste that has not been processed well. Craftsmen are accustomed to treating waste traditionally. Therefore there is a need for a crusher or grinder that can be used to crush waste into finer flakes quickly and easily. The stages used in manufacturing the machine are field observations and reviews, designing machine prototypes, identifying product specifications, and manufacturing and testing grinder machines. The results found that the grinder machine with dimensions of 90 x 50 x 120 with 24 beaters, 5 frames, 3mm tubes and 1.6 mm funnels. This engine is driven by an 8hp diesel drive. This machine can be used easily by craftsmen to treat waste in the form of fine powder. Keywords: grinder machine, waste treatment, earthenware, roof tiles, bricks